Evaluation of engineering and economic feasibility of micro-hydropower plant project - Monton Wongphat (2018)
© 2015 IEEE. This paper presents an evaluation of engineering and economic feasibility of micro-hydropower plant project. The studied site is located at Thanthong village, Mea-On district, Chiang Mai province. The engineering feasibility studies in this project are using 4 different methods of rate of water flow, which are the average runoff from streamflow gauging station, flow rate from floats method, flow rate from current meter and Manning equation. The experimental and calculation results at 100% flow rate for hydropower generation installed capacities for hydropower plant of each method are 86, 44, 54 and 181 kW, respectively. In addition, this hydropower plant can generate power at 349, 175, 218, and 786 MWh per year, respectively. In term of economy feasibility, Manning equation method has the highest Internal Rate of Return (IRR) at 58.74%, which is comparted with streamflow gauging station method has IRR only at 25.23%. Consideration results of IRR and electric energy, it can be concluded that the accuracy of flow rate is a significant factor for evaluation of hydropower project. The accuracy of data could be collected data for long period of time as using in streamflow gauging station, not just only one year period as using in Manning equation. Therefore, the streamflow gauging station method is an appropriated tool for using in feasibility study of micro-hydropower plant project.